Peer review of the pesticide risk assessment for the active substance acibenzolar‐S‐methyl in light of confirmatory data submitted. (8th July 2021) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Borroto, Jorge; Castoldi, Anna Federica; Chiusolo, Arianna; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; Ferilli, Franco; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessment carried out by the competent authority of the rapporteur Member State, France, for the pesticide active substance acibenzolar‐S‐methyl are reported. The context of the peer review was that requested by the European Commission following the submission and evaluation of confirmatory information with regard to the endocrine disruption potential of the substance. The conclusions were reached on the basis of the evaluation of the representative uses of acibenzolar‐S‐methyl as a plant activator on pome fruit, tomato and tobacco. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Assessments not finalised together with the missing information identified as being required by the regulatory framework are listed.